Malignant meningioma with intra- and extra-cranial extension: A case report (Indian Journal of Case Reports, 2018)
Meningioma is the most common intracranial benign neoplasm. The malignant transformation of this neoplasm is less frequent. Here, we report the case of a 77-year-old male patient who came to our department with a visible mass in the scalp for 1½ years. The mass was gradually increasing in size, soft in nature, not painful, and associated with the left-sided weakness. His multidetector computed tomography showed lesion which is having an intracranial component with the destruction of a vault with extracranial extension. This imaging modality gives a clear-cut picture of the extent of the lesion, nearby structures, and vascularity to give the surgeon proper guidance in two, three, and four dimensions.